Pengaruh Motivasi dan Persepsi Wisatawan terhadap Pertunjukan Musik Angklung Malioboro sebagai Daya Tarik Wisata di Kota Yogyakarta - Faluti, M Zacky; Baiquni, Muhammad; Priyambodo, Tri Kuntoro (Sekolah Vokasi, Universitas Gadjah Mada, 2022)
The study of music in tourist destinations has been developed in recent years in Europe, the United States, and Asia. However, previous studies overlook the role of traditional music in urban tourism destinations, specifically in Indonesia. Music is essential to promote an urban destination, build destination image, lighten tourists’ mood, as well as create and improve experience values during destination visits. The present study aims to explore further tourist motivation and perception who watch angklung performances in Malioboro, Yogyakarta. It is also consistent that Yogyakarta is a popular destination for its culture and arts. The way how music affects tourist motivation and perception requires further investigation. Data was collected quantitatively by online survey, observation, as well as and interview to validate findings. The results show that there is a positive and significant influence among tourist motivation and perception of angklung performances, as a tourist attraction. Moreover, a lack of collaboration occurs between angklung players, destination managers, and stakeholders. This study suggests holistic information in terms of tourist motivation and perception towards musical performances within the urban destination, and practical implications for future research, as well as management of tourism destination development.